Role transition: A descriptive exploratory study of assistant nurse clinicians in Singapore. (3rd September 2018) - Choo, Pey Jia; Tan, Jeremiah Yen Tye; Ong, Lay Teng; Aw, Ai Tee; Teo, Lee Wah; Tan, May Leng Mabel; Mohd Bte, Yusoff Azizah; Lee, Kah Keow; See, Min Ting Alicia; Lim, Siew Hoon; Ang, Shin Yuh; Lopez, Violeta
Abstract: Aim: To explore the role‐transition experiences of assistant nurse clinicians after their first year of appointment. Background: The National Nursing Taskforce was set up in Singapore to examine the professional development and recognition of nurses. It created the assistant nurse clinician role as an avenue for the nurses' career development. The role was intended to assist nurse managers to guide the nursing team in the assessment, planning, and delivery of patient care. Methods: A qualitative descriptive study design was adopted. A purposive sample of 22 registered nurses from six acute care institutions and two polyclinics in Singapore participated in the face‐to‐face interviews. An inductive content analysis approach was used to analyse the data. Results: Four themes emerged: (a) promotion to assistant nurse clinician is a form of recognition and vindication; (b) there was uncertainty about the expected role of the assistant nurse clinician; (c) experience eases transition; and (d) there was a need for peer support, mentorship, and training. Conclusions: The job description of the assistant nurse clinician needs to be better defined to provide greater clarity about their clinical and administrative duties and what is expected of their performance. Implications for Nursing Management: It is essential for nurse managers to provide successful role‐transition strategies to help the newly appointed assistant nurse clinicians to become efficient and effective leaders.